Penentuan Fraksi Aktif Antimalaria Ekstrak N-Heksana Daun Melicope Triphylla Dengan Target Inhibitor Pada Enzim Malate Quinone Oxidoreductase Plasmodium Falciparum (PfMQO) - Chrysella Rahayu (2020)
Malaria is an infectious disease caused by Plasmodium which is transmitted through the bite of a female Anopheles mosquito. In Indonesia, Papua and West Papua are malaria endemic areas with highest Annual Parasite Incidence. That situation is getting worse because of the resistance from antimalarial drugs. MQO enzyme is a new target site for malaria treatment. Based on previous research data, it is known that the n-hexane extract of M.triphylla leaves is active as an antimalarial with a mechanism of inhibiting the PfMQO enzyme with an IC50 value of 7.49 μg/mL. The study aims to find an active fraction of n-hexane extract of M.triphylla leaves. Extract fractionation process was carried out by column chromatography method and produced seven fractions. Antimalarial testing of seven fractions was carried out using two methods namely cell base (LDH assay) and enzymatic base (MQO enzyme). LDH assay results show that F6 has the highest antimalarial activity with an IC50 value 2,54 ± 0,04 μg/mL and from the results of the MQO enzymatic method it was found that F6 had the activity of inhibiting the MQO enzyme with an IC50 value 14,73 ± 0,03 μg/mL. The fraction was followed by phytochemical screening, and from phytochemical screening it was found that F6 contained terpenoids and polyphenols known as active antimalarial compounds.